# What is x y in system sq root(x+y) + (x-y) cube root =6 6root((x+y)^3(x-y)^2)=8 (x+y)^3(x-y)^2 are unnder 6root

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted on

The formulation of problem is equivocal because of misuse of mathematical symbols, hence, supposing that you want to solve the following system of equations, yields:

`{(sqrt(x+y) + root(3)(x - y) = 6),(root(6)((x+y)^3(x-y)^2) = 8):}`

You need to re-write the bottom equation such that:

`root(6)((x+y)^3(x-y)^2) = (x+y)^(3/6)*(x-y)^(2/6)`

`root(6)((x+y)^3(x-y)^2) = (x+y)^(1/2)*(x-y)^(1/3)`

`root(6)((x+y)^3(x-y)^2) = sqrt(x + y)*root(3)(x - y)`

You should come up with the following substitution, such that:

`{(sqrt(x + y) = t), (root(3)(x - y) = v):}`

Changing the variables, yields:

`{(t + v = 6),(tv = 8):}`

You need to replace `6 - t` for `v` in the bottom equation, such that:

`{(v = 6 - t),(t(6 - t) = 8):} => {(v = 6 - t),(-t^2 + 6t = 8):} => {(v = 6 - t),(t^2 - 6t + 8 = 0):}`

You should use quadratic formula to evaluate `t_(1,2)` , such that:

`t_(1,2) = (6+-sqrt(36 - 32))/2 => t_(1,2) = (6+-2)/2`

`t_1 = 4 ; t_2 = 2 `

`v_1 = 2; v_2 = 4`

Replacing 4 for `sqrt(x + y)` and 2 for `root(3)(x - y)` yields:

`sqrt(x + y) = 4 => x + y = 16`

`root(3)(x - y)= 2 => x - y = 8`

`x + y + x - y = 24 => 2x = 24 => x = 12 => y = 4`

Replacing 2 for `sqrt(x + y)` and 4 for `root(3)(x - y)` yields:

`sqrt(x + y) = 2 => x + y = 4`

`root(3)(x - y)= 4 => x - y = 64`